Identification of Key Drivers of Social Responsibility Based on Employee Health and Well-being - Zakariyanezhad, Zinat; Mehrara, Asadollah; Deiri, Einolah (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The objective of this study was to identify the key drivers of social responsibility based on the health and well-being of employees at Mazandaran University of Medical Sciences. Methods and Materials: The study was applied in terms of purpose and used a quantitative research approach with the cross-impact matrix method. The statistical population included all managers, deputies, and administrative staff at Mazandaran University of Medical Sciences, who have expertise in the areas of management, human resources, health, and well-being, and who were employed in the administrative, clinical, educational, research, and technology sectors during the academic year 2023–2024. Based on sample size determination using structural equation modeling, 237 individuals were selected through a convenience sampling method. The research tool was a questionnaire derived from interview data. The validity of the questionnaire was confirmed based on content, face, and construct validity. Additionally, the reliability of the scale was reported with a Cronbach’s alpha coefficient of 0.94. For data analysis, confirmatory factor analysis and the cross-impact matrix method were employed using LISREL and MICMAC software. Findings: Based on the results of MICMAC software and 16 factors extracted from the opinions of experts, seven major factors were identified as key drivers of the social responsibility model based on employee health and well-being at the university: attention to human resource well-being and health, organizational attitude and commitment, laws and regulations, effective management, evaluation and supervision, cultural promotion, and individual characteristics. Conclusion: The results indicated that the model of key drivers of social responsibility based on health and well-being had good fit, and the key drivers exerted a relatively strong indirect impact on each other.